Kurma Sebagai Alternatif untuk Meningkatkan Kadar Hemoglobin Ibu Hamil dengan Anemia - Zulhaini Sartika Aliaman Pulungan; Ahmady Ahmady; Edi Purnomo (FORIKES, 2021)
Anemia is the main cause of the high maternal mortality rate in Indonesia. Dates are one of the supplements that can increase iron levels in pregnant women. This study aims to determine the increase in hemoglobin levels of pregnant women with anemia after administration of date palm juice. The design of this study was non-randomized pre-test and post-test with control group. The sample consisted of 30 pregnant women in the city of Mamuju who were selected by purposive sampling technique. Data were collected by direct examination, then analyzed using paired sample t-test and independent sample t-test. The results showed that there was no difference in hemoglobin levels between before and after administration of Fe tablets in the control group (p value = 0.157; and there was a difference in hemoglobin levels between before and after administration of Fe tablets and date juice in the intervention group (p value = 0.005). Independent sample t-test showed that there was no difference in the increase in hemoglobin levels between the control group and the intervention group (p value = 0.394). Although there was no significant difference, the hemoglobin levels of anemic pregnant women who were given Fe tablets and date juice increased by 1 ,16 g/dl (12.78%) compared to those given Fe tablets alone, an increase of only 0.5 g/dl (5.19%). This indicates that date palm juice can be used as an alternative supplement to increase hemoglobin levels. pregnant women with anemia. Keywords: anemia; pregnant mother; dates; date juice ABSTRAK Anemia adalah penyebab utama angka kematian ibu di Indonesia. Kurma merupakan salah satu suplementasi yang dapat meningkatkan kadar zat besi pada ibu hamil. Penelitian ini bertujuan untuk mengetahui peningkatan kadar hemoglobin ibu hamil dengan anemia setelah pemberian sari kurma. Rancangan penelitian ini adalah non randomized pre test and post test with control group. Sampel ada 30 ibu hamil di kota Mamuju yang dipilih dengan teknik purposive sampling. Data dikumpulkan dengan pemeriksaan langsung, lalu dianalisis menggunakan paired sample t-test dan independent sample t-test. Hasil penelitian menunjukkan bahwa tidak ada perbedaan kadar hemoglobin antara sebelum dan sesudah pemberian tablet Fe pada kelompok kontrol (nilai p = 0,157; dan ada perbedaan kadar hemoglobin antara sebelum dan sesudah pemberian tablet Fe dan sari kurma pada kelompok intervensi (nilai p = 0,005). Independent sample t-test menunjukkan bahwa tidak ada perbedaan peningkatan kadar hemoglobin antara kelompok kontrol dan kelompok intervensi (nilai p = 0,394). Walaupun tidak ada perbedaan yang signifikan, namun kadar hemoglobin ibu hamil dengan anemia yang diberi tablet Fe dan sari kurma mengalami peningkatan sebesar 1,16 g/dl (12,78%) dibandingkan yang diberi tablet Fe saja, mengalami peningkatan hanya sebesar 0,5 g/dl (5,19%). Hal ini menunjukkan bahwa sari kurma dapat digunakan sebagai alternatif suplemen untuk meningkatkan kadar hemoglobin ibu hamil dengan anemia. Kata kunci: anemia; ibu hamil; kurma; sari kurma